Šaukėnų šnektos veiksmažodžio asmenavimo sistema (vientisinės formos) - Rosinas, Albertas (Baltistica, 2009)
THE VERBAL CONJUGATION SYSTEM OF THE ŠAUKĖNAI SUBDIALECT (SIMPLE FORMS)The Šaukėnai subdialect belongs to the northern subdialects of the southern Žemaitian dialect and has retained their most characteristic features.However, due to considerable theoretical and practical obstacles, the description of the formation of the derived verbal forms in the Šaukėnai subdialect by applying the rules of the formation of derived verbal forms in Standard Lithuanian is impossible.The verb of the Šaukėnai subdialect possesses the morphological categories of person, number, tense, mood and voice. The inflected verbs (except the imperative mood) have three singular and three plural forms. The 3rd person form is neutral with respect to the category of number, it denotes an action performed either by one or more than one agent. The marked member of the opposition singular / plural is the plural. The verb of the Šaukėnai subdialect possesses both simple and compound tenses.In the Šaukėnai subdialect, the paradigms of verbal forms indicate three types of modal oppositions: they distinguish four moods, i.e. indirect, direct, imperative and subjunctive. The direct and indirect moods possess the tense forms of present, past, past frequentative and future whereas the imperative and subjunctive moods do not possess the category of tense.In the Šaukėnai subdialect, there are two verbal conjugations which are distinguished according to the underlying form endings in the present tense of the indicative mood. The 1st conjugation comprises verbs whose present tense underlying form ending is a zero morph (O) which is preceeded either by a consonant or –j, e.g. vèd, tí·l̑, šuokiníe, kaũlij, the 2nd conjugation comprises verbs whose present tense underlying form ends in /-a/, e.g. mãt-a, bìj-e, žìn-a, etc.The underlying simple past verbal forms of the 1st ( or (i̯)a-stem) conjugation end in /-a/ or /-i/, cf. rãd-a, lìj-e and ãr-i.The a-stem verbs constitute a highly productive and stable class while in the subdialect there have remained only four i̯a (former i) - stem verbs: tí·l̑ : ti·líeti, gál̑ : galíeti, mí·l̑ : mi·líeti  and gúl̑ : gulíeti. The verbs of the 2nd conjugation (or a-stem) are also rather productive.The Šaukėnai subdialect has preserved some remnants of athematic conjugation. Some verbs are impersonal, e.g. per̃št, the others possess all personal forms derived from underlying form stems, e.g. mĩ·i̯ktu, etc.The categories in the Šaukėnai subdialect indicate a variety of symbolization.The categories of person and number are usually represented by grammatical morphemes, or endings (i.e. the morphological markers of the categories): /-u/, /-a·u/symbolize the categories of person and number, i.e.  the 1st person and the singular, /-i/, /-a· /, /-e· / -- the 2nd person and the singular /-am/, /-uom/, /-iem/, /-ma/--  the 1st person and the plural, /-at/, /-uot/, /-iet/, /-te/-- the 2nd person and the plural. The ending forms of the 3rd person represent the category of person, i.e. the 3rd person only.The article rejects the opinion, which dominates in Lithuanian linguistic literature, as if the verbal form endings could also represent the category of tense. It is complete misunderstanding, cf. sak-á·u (present) and suk-á·u (past), mùš-ù (present) and mùš-ù (future), etc. As evidenced by the data from the Šaukėnai subdialect, the tense can be expressed by syntactic category markers, phonological means, cf. mat-á·u and mač̑-ǽ·u, various formants (infixes), such as –n-, -st-, -s-, cf. añk and ãka, ki̲m̃b and kì̲ba, ti̲r̃pst  and ti̲r̃pa, dí̲́rbu and dí̲́rpsu, suffixes, cf. dí̲́rb-a·u and dí̲́rb-dav-a·u as well as vowel gradation, cf. ker̃t and ki̲r̃ta, etc. However, only the simple form endings of the indicative and subjunctive moods can express the mood.The forms of the subjunctive mood, alongside their specific endings, possess a distinctive formant, -t- while the forms of the imperative mood differ from the forms of the other moods only in the underlying form which has a specific suffix, -k. The above suffix is the basis for the formation of plural forms whose endings do not express the category of mood. The verbal forms in the Šaukėnai subdialect are derived from the underlying forms (see the list in the article) according to the additive rules by adding corresponding endings. The categoric asymmetry is realized additively. Therefore the coding of the derived forms is either maximally or minimally iconic.
Keywords: Šaukėnai; veiksmažodis; asmenavimas